The Influence of Terminal Booking System (TBS), Yard Operation Plan (YOP), Turn Round Time (TRT) on Operational Effectiveness PT Pelindo Terimnal Peti Kemas Semarang - Rifqi, Zenda Fathur; Mashudi, Mashudi (Asian Journal of Logistics Management, 2023)
PT Pelindo Terminal Peti Kemas Semarang (TPKS) is a subholding of PT Pelindo that focuses on export and import container services. TPKS is one of the pioneers of the smart port concept in Indonesia, one of which is by implementing the Terminal Booking System (TBS) and Yard Plan to reduce Turn Round Time (TRT). However, in practice there are still many discrepancies between booking and gate-in hours, which have an impact on operational activities. The purpose of this study is to determine the effect of the Terminal Booking System, Yard Operation Plan, Turn Round Time both partially and simultaneously and to see the factors that most influence the operational effectiveness of TPKS. This study used a quantitative method of explanatory format with a population of planning, control and operational management divisions using total sampling. The results of this study indicate that there is a positive and significant influence between the Terminal Booking System, Yard Operation Plan, Turn Round Time both partially and simultaneously on the operational effectiveness of TPKS. Meanwhile, the most influential factor is the Turn Round Time variable. The conclusion is that there is a positive and significant influence between TBS, YOP, and TRT either partially or simultaneously on the operational effectiveness of TPKS. The researcher's suggestion for PT Pelindo TPKS is to be able to optimize loading and unloading activities and receiving delivery in domestic CY (Container Yard).